Вероятностный прогноз образования затворов в нижнем бьефе строящейся Богучанской ГЭС при затоплении водохранилища - Стефанишин, Д.Ф.; Романчук, Е.Г. (Екологічна безпека та природокористування, 2012)
Given are the results of probabilistic forecasting ofice clogging in the downstream of Bohuchanskaja hydroelectric plant that built on the river Angara in the first filling the reservoir.